2010
DOI: 10.4274/tftr.56.135
|View full text |Cite
|
Sign up to set email alerts
|

Approach to the Frail Elderly

Abstract: Ö Öz ze et tK›r›lgan yafll› sendromu, geriatrik sendromlardan biri olup, oluflan strese artm›fl hassasiyet olarak tan›mlanmakta ve birbiri ile iliflkili pek çok sistemde bozulma ile seyretmektedir. Yayg›n semptom ve bulgular›; istemsiz kilo kayb›, kas güçsüzlü¤ü, yorgunluk, yürüme h›z›nda azalma ve fonksiyonlarda ilerleyici kay›pt›r. K›r›lgan yafll›n›n tedavi yönetimi en zorlu tablolardan birisidir. Tedavi edici yaklafl›mlar; nutrisyonel destek, uygun egzersiz program›, çok yönlü geriatrik de¤erlendirme yan›nd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
3
0
2
Order By: Relevance
“…According to the FRAILTURK project, the frequency of frailty is reported to be 39.2% in Turkey (Eyigor et al, 2015). The result of a decline in reserve and function across multiple physiological systems, frailty causes older people to lose the ability to cope with everyday life stressors (Akın et al, 2015; Artaza-Artabe, Sáez-López, Sánchez-Hernández, Fernández-Gutierrez, & Malafarina, 2016; Boutoleau-Bretonnière & Vercelletto, 2009; Çakmur, 2015; Eyigör & Kutsal, 2010; Santos-Eggimann, Cuénoud, Spagnoli, & Junod, 2009). Frailty negatively affects all dimensions of life and frail older adults face deterioration in their quality of life from anxiety, depression, difficulties in fulfilling daily living activities, and reduced life satisfaction (Aslan & Keskin, 2015; Hubbard, Goodwin, Llewellyn, Warmoth, & Lang, 2014; Uchmanowicz & Gobbens, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…According to the FRAILTURK project, the frequency of frailty is reported to be 39.2% in Turkey (Eyigor et al, 2015). The result of a decline in reserve and function across multiple physiological systems, frailty causes older people to lose the ability to cope with everyday life stressors (Akın et al, 2015; Artaza-Artabe, Sáez-López, Sánchez-Hernández, Fernández-Gutierrez, & Malafarina, 2016; Boutoleau-Bretonnière & Vercelletto, 2009; Çakmur, 2015; Eyigör & Kutsal, 2010; Santos-Eggimann, Cuénoud, Spagnoli, & Junod, 2009). Frailty negatively affects all dimensions of life and frail older adults face deterioration in their quality of life from anxiety, depression, difficulties in fulfilling daily living activities, and reduced life satisfaction (Aslan & Keskin, 2015; Hubbard, Goodwin, Llewellyn, Warmoth, & Lang, 2014; Uchmanowicz & Gobbens, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Deliryumun ileri yaş grubunda, fonksiyonel bozulma, bağımsızlık kaybı ve ölüm gibi olaylar zincirinin başlatıcı veya anahtar parçası olduğu düşünülmektedir. Toplumdaki genel prevalansı %1-2 olmasına karşın, genel hastane yatışına baktığımızda bu oran %14-24'lere çıkmaktadır (23)(24)(25) . Hastaneye yatış döneminde ise, özellikle postoperatif, yoğun bakım, subakut ve palyatif bakım kliniklerinde, sıklık %6'dan %56'lara kadar artabilmektedir.…”
Section: Discussionunclassified
“…Patofizyoloji tam olarak anlaşılmış değildir. Ancak şu andaki kanıtlar; ilaç toksikasyonu, inflamasyon ve akut stres yanıtlarının nörotransmisyonunda bozulmaya neden olarak deliryum tablosu yarattığı yönündedir (19,24,25) . Preoperatif dönemde kesin suretle kognitif fonksiyonlar değerlendirilmelidir.…”
Section: Discussionunclassified
“…Variations in swallow sound characteristics associated with different swallowing efforts—forceful, normal, and easy swallowing—have been documented 40 . A study by Borr et al 18 compared differences in swallow sound characteristics between people of different ages, and Eyigör et al 63 found a correlation between acoustic variability at the onset of swallowing and age. A study by Cichero and Murdoch 64 observed gender-related and age-related variations in swallow sound characteristics.…”
Section: Characteristics Of Swallowing Soundsmentioning
confidence: 99%